Diversity Among Pearl Millet Landraces Collected in North-western India - Yadav, O P; Rattunde, E Weltzien; Bidinger, F R (Annals of Arid Zone, 2016)
Evaluation of genetic diversity among germplasm accessions is important to plalll breeders who desire sources of genes for particular traits. In this study. 105 landraces of pearl millet (Pellllisell//ll glaltcl//Il) collected from north-western India were evaluated for two seasons at three locations that resembled to the collection sites of landraces. Significant genetic diversity was observed for all eight morphological traits evaluated. Time to !lower ranged from 50 to 64 days. panicle length from 19 to 37 cm and plant height horn 177 to 223 cm. Number of panicles plan(1 varied between 0.8 and 3.8. The range in grain and stover yielding ability of landraces was more than two-fold. Landraces could be differentiated into nine clusters of phenotypic diversity. Clusters 2 and 5 proved to be the largest ones consisting of 24 to 25 accessions. while clusters I. 3. 4. and 6 were composed of a sillall number (3 to 8) of landrace accessions. There were some correspondence between the geographic collection site of landraces and their inclusion in particular clustcrs. Some landraces collected from adjacent areas tended to fall in different clusters indicating the existence of good diversity even within small geographic regions.